Challenges and Approaches to Scaling the Global Commons - Fritsch, Felix; Emmett, Jeff; Friedman, Emaline; Kranjc, Rok; Manski, Sarah; Zargham, Michael; Bauwens, Michel (Frontiers in Blockchain, 2021)
The re-emergence of commoning over the last decades is not incidental, but rather indicative of a large-scale transition to a more ‘generative’ organisation of society that is oriented towards the planet’s global carrying capacity. Digital commons governance frameworks are of particular importance in this historical conjuncture, as they allow for scaling the organization of communities around common goals and resources to unprecedented levels of size, complexity and granularity. Distributed Ledger Technologies (DLTs) such as blockchain have lately given new impetus to the emergence of a new generation of authentic ‘sharing economy’, protected from capture by thorough distribution of power over infrastructure, that spans not only digital but also physical production of common value. The empirical exploration of the frontiers of DLT-based commoning at the heart of this article considers three exemplary cases for this new generation of commons-oriented community frameworks: the Commons Stack, Holochain and the Commons Engine, and the Economic Space Agency. While these projects differ in their scope as well as in their relation to physical Common Pool Resources (CPRs), they all share the task of redefining markets so as to be more conducive to the production and sustainment of common value(s). After introducing each of them with regards to their specificities and commonalities, we analyse their capacity to foster commons-oriented economies and “money for the commons” that limit speculation, emphasize use-value over exchange-value, favor equity in human relations, and promote responsibility for the preservation of natural habitats. Our findings highlight the strengths of DLTs for a federated scaling of CPR governance frameworks that accommodates rather than obliterates cultural differences and creates webs of fractal belonging among nested communities.